Disclosing haemophilia at school: strategies employed by mothers of children with haemophilia in Japan. (9th April 2015) - Seki, Y.; Kakinuma, A.; Kuchii, T.; Ohira, K.
<x xml:space="preserve">Abstract</x> Introduction Most children with haemophilia in Japan study in mainstream schools. However, many mothers have difficulty deciding whether to inform teachers of their child's haemophilia because of the accompanying potential discrimination and prejudice, particularly after the press coverage on the HIV scandal in the 1980s. Aims We therefore aim to explore and describe disclosure strategies of mothers of children with haemophilia. Methods A qualitative study was conducted using the modified grounded theory approach to explore disclosure strategies of mothers of children with haemophilia. Semi‐structured interviews were conducted with 19 selected mothers (12 children were HIV positive and 7 were HIV‐negative). Results In the pre‐HIV/AIDS crisis period, the kind of strategy employed – full disclosure, conditional full disclosure and partial disclosure – depended on the extent of mothers' fears about mainstream schools refusing admission because of their child's haemophilia. After the HIV/AIDS crisis in the 1980s in Japan, the three categories of strategies employed by mothers of children with haemophilia were limited disclosure, non‐disclosure and full disclosure. These depended on mothers' expectations of discrimination towards their child because of the social stigma around haemophilia and being HIV‐positive. Conclusion For children with haemophilia to feel safe attending school, public schools must establish care management and anti‐discrimination systems for children with chronic diseases, thus assuring parents of their children's welfare at school.